ROBOT LINE FOLLOWER PENGANTAR SURAT MENGGUNAKAN METODE FUZZY LOGIC STUDI KASUS FAKULTAS TEKNIK UNIVERSITAS PANCASILA - putri, andini; Maspiyanti, Febri (Jurnal Teknologi Terpadu, 2017)
Mail delivery at the Faculty of Engineering Pancasila University (FTUP) has many complaints regarding the delay of mail delivery from the administrative officer to the recipient of the mail. Lack of administrative staff responsible for the delay of mail acceptance can certainly cause great disadventages to the recipient; hence this can be a big factor inhibiting the dissemination of information. As technology develops, many research on robot able to accommodate human’s work. One type of robot that has been developed is the Robot Line Follower. In order to reduce the mail delivery delay, in this research we built a Line Follower Robot using Fuzzy Logic method. Fuzzy logic applied to this robot as a determinant of Servo motor speed and distance determinant of mail delivery area. This research yields 100% accuracy for straight line, 79% accuracy for U-line, 53% accuracy for 90o turn, 94,75% accuracy for obstacle detection, 87,75% accuracy for alarm, and 92,75% accuracy for RFID card detection, and 82% accuracy for RFID Card with option menu. Keywords: Accuracy, Fuzzy logic, Line Follower, RFID, Robot